Comparative Proteomics Analysis for Elucidating the Interaction Between Host Cells and Toxoplasma gondii - Sun, Hui; Li, Jin; Wang, Longjiang; Yin, Kun; Xu, Chao; Liu, Gongzhen; Xiao, Ting; Huang, Bingcheng; Wei, Qingkuan; Gong, Maoqing; Cao, Jianping (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii, a representative model organism belonging to the phylum Apicomplexa, can infect almost all warm-blooded organisms, including humans. The invasion of host cells via host–parasite interaction is the key step for T. gondii to complete its life cycle. Herein we performed tandem mass tag analysis to investigate global proteomic changes in host cells (human foreskin fibroblasts, HFFs) [HFFs infected with T. gondii (HT) vs. HFFs (H)] and T. gondii [HT vs. T. gondii (T)] during intracellular infection. Overall, 3477 and 1434 proteins were quantified, of which 375 and 1099 proteins were differentially expressed (adjusted p-value < 0.05 and >1.5 or <0.67-fold change) in host cells and T. gondii, respectively. T. gondii invasion relies on the secretion of numerous secretory proteins, which originate from three secretory organelles: micronemes, rhoptries, and dense granules. In the HT vs. T group, few secretory proteins were upregulated, such as microneme proteins (MICs: MIC6, MIC10), rhoptry bulb proteins (ROPs: ROP5, ROP17), and dense granule proteins (GRAs: GRA4, GRA5, GRA12). In contrast, dozens of known secretory proteins were significantly downregulated in T. gondii-infected HFFs. In HFFs, gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses revealed a large number of differentially expressed proteins (DEPs) enriched in metabolic processes and immune-associated signaling pathways, such as NF-κB, cAMP, and Rap1 signaling pathways. Further, in case of T. gondii, DEPs were involved in ribosome biogenesis, citrate cycle, and galactose metabolism, indicating that cell biosynthesis and metabolism of T. gondii were altered after host cell invasion. These findings reveal novel modifications in the proteome of host cells as well as T. gondii, helping us better understand the mechanisms underlying host–parasite interaction.